THE ROLE OF EDUCATIONAL MEDIA IN INCREASING INTEREST IN LEARNING MATHEMATICS IN ELEMENTARY SCHOOL - Muhamnad Rofi' Anugroho Rino (CV. Fahr Publishing, 2025)
This study investigates the role of educational media in enhancing elementary students’ interest in learning mathematics, a subject often perceived as abstract and disengaging at early educational levels. The primary objective is to explore which types of instructional media—such as digital games, interactive videos, and augmented reality—are most effective in fostering student interest and how contextual variables like teacher competence and infrastructure influence their effectiveness. Employing a library research method, this study systematically reviewed empirical studies from the last five years, utilizing thematic analysis to identify key patterns and gaps. The findings reveal that highly interactive media, particularly game-based and augmented reality tools, significantly increase students' enthusiasm and motivation toward mathematics when supported by relevant content and capable facilitation. A key novelty of this study lies in its emphasis on the affective outcomes of learning—specifically interest—rather than solely cognitive achievements, and in its integration of contextual factors often overlooked in previous studies. Additionally, the study contributes a conceptual framework connecting media types, classroom context, and sustained student interest. The results underscore the importance of aligning educational media with learners’ developmental needs and school environments to optimize engagement. In conclusion, the study provides a comprehensive foundation for future research and practical implementation, especially for educators and policymakers aiming to revitalize mathematics learning in primary education through technology-enhanced instruction.